Analisis Penerapan Digitalisasi Laporan Keuangan pada Usaha Kecil (Studi pada Usaha Kecil Kuliner di Kota Pangkalpinang) - Tiara Fitari; Lasmi Hartati (Universitas Bangka Belitung, 2022)
: Digitization is the process of converting from analog to digital. The process of changing to digital has various goals, including work automation, minimizing paper use and also reducing costs. Financial statements have benefits for several parties such as investors, employees, creditors, suppliers, customers, governments and other parties. So that financial statements become very important information. However, recording financial statements manually by small businesses is sometimes difficult due to limitations, causing the company's financial statements to be uninformative and difficult to read. The limitation that is often faced by business actors is an educational background that does not understand accounting or bookkeeping, or lacks discipline in recording and others. Digitization is the right answer to overcome the limitations that occur in these small businesses. Digitizing financial statements is the process of changing the recording of transactions that occur manually into digital form. The purpose of this study is to find out how to apply digitalization of financial reports to small businesses in the culinary field in Pangkalpinang City.The type of research used is descriptive research that illustrates how the application of digitalization of financial statements there is a small business in the culinary field in the city of Pangkalpinang. The data collection techniques used by researchers are interviews and documentation. The focus in this research is financial statements and digitalization of financial statements. Haisl research shows 9 of 20 small business samples in the culinary field in Pangkalpinang have not used the digitalization of financial statements. The factors that cause this are because business actors believe that the business activities they run do not require digital recording can still be done manually. In addition, the amount of income and profit in the business so it is necessary to make it easier for business operations, and also the knowledge of business actors. Business actors who cannot keep up with technological developments are difficult to apply the digitalization of financial statements, so that it becomes a business obstacle that needs to be considered by the government.